P51 Interferon-induced fatigue in hepatitis C infected patients is associated with increased expression of indoleamine 2, 3-dioxygenase in peripheral blood mononuclear cells. (6th September 2011) - Gess, M; Forton, D; Myint, A M
Abstract : Introduction: Interferon-α (IFN)-based antiviral therapy for chronic hepatitis C virus (HCV) infection commonly induces fatigue and depression. IFN-induced symptoms may result from the activation of indoleamine 2, 3-dioxygenase (IDO), the rate-limiting enzyme, regulating the breakdown of tryptophan (Trp) into L-kynurenine (Kyn), expressed in immune cells and brain. IDO activation might result in Trp and serotonin depletion and accumulation of neurotoxic Kyn metabolites. IFN increases IDO gene expression in vitro and increased serum Kyn/Trp ratios have been reported in IFN-treated patients. However, a consistent relationship between Kyn/Trp and IFN-induced symptoms in HCV has not been shown. Aim: We sought to determine the relationship between IDO mRNA expression in PBMC, serum Kyn/Trp ratio and IFN-induced symptoms. Method: Fatigue Impact Scale (FIS) and Hospital Anxiety and Depression (HADS-D) questionnaires were completed by 19 patients at baseline and after 12 weeks treatment with PEGIFN-2a and ribavirin. Blood samples were taken from patients and 14 healthy controls. Total RNA was extracted from Ficoll separated PBMC and IDO mRNA was quantified relative to GAPDH using RT-PCR (Applied Biosystems). Expression at week 12 vs baseline was calculated as fold change using the 2 −ΔΔCt -method. Serum Kyn/Trp was measured using HPLC/MS/MS. Results: IDO mRNA expression at baseline was similar in HCV patients and controls (ΔCt=9.76±0.39, ΔCt=9.73±0.28, p=NS). In the whole cohort, there was no change in IDO expression at week 12 vs baseline (ΔCt=10.0±0.23 vs ΔCt=9.76±0.39, p=NS), although serum Kyn/Trp increased significantly (p<0.001). However, patients with IFN-induced fatigue (ΔFIS>20; n=7) showed increased IDO mRNA expression (ΔΔCt= −0.97±0.58; median fold change =2.57) vs those without fatigue (ΔΔCt=0.96±0.53; mfc=0.89; p=0.02). Only modest increases in depression scores were seen (ΔHADS-D ≥5 in 5 patients) but no differences in ΔΔCt were seen compared to those with unchanged HADS-D. Baseline IDO mRNA expression was not predictive of IFN-induced fatigue or depression. There were no associations between baseline or week 12 Kyn/Trp ratios and IFN-induced fatigue or depression. Conclusion: We show for the first time that peripheral IDO gene expression in HCV patients is similar to healthy controls and IFN-treatment leads to differential induction of IDO mRNA. IFN-induced fatigue is significantly associated with increased peripheral IDO expression but not serum Kyn/Trp. Measurement of PBMC IDO mRNA may mirror CNS changes more accurately than peripheral Trp and Kyn levels. The modest prevalence of depression in this small cohort may explain the lack of association with depression.